2007
DOI: 10.1002/aoc.1207
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of outdoor settled dust by butyltins in Malta

Abstract: The presence of compounds of tributyltin (TBT), dibutyltin (DBT) and monobutyltin (MBT) was determined in outdoor settled dust collected from several sites on the island of Malta, mainly from flat rooftops of school buildings. The dust was separated into three size fractions with diameters (µm) >250, 125-250 and <125, and the two finer fractions were analysed for butyltins using extraction with glacial acetic acid followed by derivatization/solvent extraction with sodium tetraethylborate in the presence of iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In water, concentrations of 0.0002 μg/l (Directive 2008/105/EC) are considered to be safe, and for the sediment, the proposed safe value is 0.02 μg/kg DW (Environmental Quality Standards (EQS) 2005 ). The high concentrations found in the boatyards in this and other studies (Decelis and Vella 2007 ) emphasize the need for EQS standards for these substances both in sediment and soil.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In water, concentrations of 0.0002 μg/l (Directive 2008/105/EC) are considered to be safe, and for the sediment, the proposed safe value is 0.02 μg/kg DW (Environmental Quality Standards (EQS) 2005 ). The high concentrations found in the boatyards in this and other studies (Decelis and Vella 2007 ) emphasize the need for EQS standards for these substances both in sediment and soil.…”
Section: Discussionsupporting
confidence: 56%
“…Dust and fine eroded particles from antifouling paint can travel relatively long distances. Turner 2010 and the references therein and several reports show high levels of TBT contamination in nearby environments (Decelis and Vella 2007 ). In one case in Thailand, elevated lead levels were found in dust from a boatyard several hundred meters from the boatyard (Maharachpong et al 2006 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Paint particles from these sources are transported to the aquatic environment as airborne particulates that are subject to fallout, with road runoff or treated waste water, or via washdown from boat maintenance facilities or coastal structures undergoing repair. The significance of the local transport of airborne paint particles has been established from the levels and signatures of contamination of soils and roof top dusts of residential and municipal buildings in the vicinity of roads, dry docks, boatyards and harbours ( Decelis and Vella, 2007 ; Jartun et al., 2009 ; Turner, 2013 ; Eklund et al., 2014 ; Sakata et al., 2017 ; Meza-Figueroa et al., 2018 ). Given the particle size range generated by sanding (in the range of < 50 nm to a few μm in diameter; Koponen et al., 2009 ), however, the potential range of airborne transport of paint particles is considerable.…”
Section: Sources Of Paint Particles To the Marine Environmentmentioning
confidence: 99%
“…Spread of TBT from boat repair activities was determined in dust collected from rooftops of houses at Malta (Decelis and Vella 2007), which suggested that dust from boat maintenance areas can have impact on adjacent terrestrial grounds. This correlates well with the findings of lead content in dust in areas surrounding a boatyard in Thailand where elevated levels in household dust was found several 100 m from the boatyard with decreasing distance to the boatyard (Maharachpong et al 2006).…”
Section: Spread Of Contaminants From Boatyardsmentioning
confidence: 99%